PENGEMBANGAN PEMBELAJARAN PENJAS ADAPTIF MELALUI MEDIA PERMAINAN BANGUN PINTAR BERWARNA PADA SISWA TUNARUNGU SDLB NEGERI SEMARANG (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the results of the adaptive learning model penjas media through smart wake -colored game at Semarang State SDLB deaf students . The game is a wake -colored smart penjas innovation in adaptive learning that is instructive . This research is a development . The analysis procedure includes product development product that will be created , developed the initial product , expert validation and revision , testing and revision of small groups , large groups and test the final product . The data was collected using a questionnaire derived from the expert evaluations and observations of students . The data analysis technique used is descriptive percentages . From the test data showed that the initial product evaluation , expert penjas 84.0 % ( Good ) , learning experts I 85.2 % ( Good ) and expert learning II 84.0 % ( Good ) small test group 87.55 % ( Good ) and field trials / large group 91.86 % ( Very Good ) . From the available data it can be concluded that the model of an adaptive learning game penjas smart wake of this color can be used for deaf students grade 2 SDLB Semarang.